2017
DOI: 10.12659/msm.903472
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Galectin-3 with the Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: BackgroundAcute exacerbation of chronic obstructive pulmonary disease (AECOPD) aggravates the overall severity in COPD patients, resulting in severe morbidity and mortality. However, there are no objective biomarkers currently available to predict the development of AECOPD. Several studies have indicated that galectin-3 (Gal-3) is involved in diseases characterized by excessive inflammatory response and fibrosis. The objective of this study was to examine the dynamic changes of Gal-3 in acute exacerbation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
2
22
0
2
Order By: Relevance
“…Gal-3 is also involved in renal fibrosis, as shown by several animal studies [51,54], and plasma levels of Gal-3 are increased in several other diseases, including chronic obstructive pulmonary disease (COPD), and several types of cancer [55][56][57]. Therefore, it is likely that the observed increases in plasma levels of Gal-3 in HF are associated with increased cardiac Gal-3 production, but also with production in other organs and/or tissues.…”
Section: Fibrosis Marker Gal-3mentioning
confidence: 98%
“…Gal-3 is also involved in renal fibrosis, as shown by several animal studies [51,54], and plasma levels of Gal-3 are increased in several other diseases, including chronic obstructive pulmonary disease (COPD), and several types of cancer [55][56][57]. Therefore, it is likely that the observed increases in plasma levels of Gal-3 in HF are associated with increased cardiac Gal-3 production, but also with production in other organs and/or tissues.…”
Section: Fibrosis Marker Gal-3mentioning
confidence: 98%
“…In addition to SCA, gal-3 levels, when increased, have already been associated with coronary remodeling promoting the development of coronary artery ectasia (CAE) (Aciksari et al, 2020). Increased serum levels of gal-3 have been observed in the patients with chronic obstructive pulmonary disease, as they were associated with systemic inflammation, which suggests that gal-3 could be a biomarker for this disease (Feng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Literature review revealed that several laboratory parameters (CRP, PCT, nitric oxide, galectin-3, L-arginine, changes in leukocyte count or formula, etc.) have been investigated in order to distinguish the exacerbation and stable periods of COPD [8][9][10][11][12][13][14]. However, there are only few studies investigating the relationship between PRG4 and COPD, and the results show that PRG4 levels increase in patients with COPD [15,16].…”
Section: Discussionmentioning
confidence: 99%